Aeon Mall Seri Manjung Court Management System / Nur Adlina Mohd Mansor - Mohd Mansor, Nur Adlina (2018)
The development of Aeon Mall Seri Manjung Court Management System (CMS) in this project is carried out as one desire to help users easily to make reservation through online. Reservation is one of the thing that most people familiar with, in order to make sure the things or space that desire to used are owned. In Aeon Mall Seri Manjung, people are gathering around used to buy some daily things for the lives but most things that get attention crowd of people is when there are some kind of promotion or shows handled at the center or any suitable area called court. Therefore, exist several person called customer who desire to get own sales by make court reservation in this mall. On the other hand, this kind of side income help increasing profit for this mall to achieve sales target every month. In order to make court reservation, customer need to contact person in charge under Promotion Department in Aeon Mall Seri Manjung which is a Supervisor, Puan Syuhada Binti Mohd Mansor. Here, the problems that have been identified is when customer having difficulty to make reservation and to get know the court reservation availability where it depends on phone call session. In contrast, supervisor also having difficulty to manage date and payment court reservation since all the information recorded in log book. CMS used Web-based environment to make sure both customer and supervisor feel flexible to reserve and manage court reservation. Hence, waterfall model methodology was applied in CMS which involving three phases which are requirement gathering and analysis, design and implementation that will help to complete this project in proper way throughout the requirement that have been gather. Findings and analysis was done to ensure that the objectives created at the beginning of this project are corresponding to each phase in methodology.